2010
DOI: 10.1111/j.1365-3083.2010.02385.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor C5a in Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: The complement component C5a is a potent inflammatory peptide, which may be involved in the pathogenesis of Chronic Obstructive Pulmonary Disease (COPD). We analysed the induced sputum and plasma of 28 patients with stable COPD, 12 healthy smokers and 7 non‐smokers. In 13 of the patients with COPD, we also observed paired samples during acute exacerbation. The concentrations of C5a/C5a desArg and C3a/C3a desArg were measured using cytometric bead array. Both C5a and C3a concentrations in induced sputum of stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
2
17
1
1
Order By: Relevance
“…Significant increases in both sputum C3a and C5a were found during COPD exacerbations compared with baseline; this was consistent with previous studies, two of which found sputum C5a elevated [1, 5] and another demonstrated C3a elevation at exacerbation [10]. The opposite was seen for serum C3a and C5a, in which we found significantly lower levels during exacerbations.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Significant increases in both sputum C3a and C5a were found during COPD exacerbations compared with baseline; this was consistent with previous studies, two of which found sputum C5a elevated [1, 5] and another demonstrated C3a elevation at exacerbation [10]. The opposite was seen for serum C3a and C5a, in which we found significantly lower levels during exacerbations.…”
supporting
confidence: 91%
“…Complement anaphylatoxins (C3a, C5a) are potent inflammatory mediators, implicated in the exaggerated inflammatory response seen in chronic obstructive pulmonary disease (COPD) [1]. COPD patients have decreased levels of serum C3 and C4 [2, 3], and higher levels of sputum C3a and C5a, than healthy volunteers [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found a correlation between the degree of the reduction of these serum proteins and the presence of symptoms of chronic bronchitis (41). In contrast, Marc and colleagues demonstrated that sputum levels of both C3a and C5a were significantly increased in patients with moderate to severe stable COPD compared with control healthy smokers and nonsmokers (42). Together this would suggest that as complement is sequestered toward the lung where it is activated and consumed, serum levels would decline.…”
Section: Discussionmentioning
confidence: 76%
“…In this study in patients with stable COPD we found elevated in vivo levels of C5a in induced sputum compared to healthy non-smoking subjects. In our later work (Marc et al 2010), we studied the airway and systemic levels of C5a and C3a in patients with COPD during the stable phase and during acute exacerbation of the disease. For this purpose we analyzed induced sputum and plasma samples of 28 patients with COPD.…”
Section: Complement Factor C5amentioning
confidence: 99%